2022
DOI: 10.1080/21505594.2022.2028484
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa adaptation in cystic fibrosis patients increases C5a levels and promotes neutrophil recruitment

Abstract: Cystic fibrosis (CF) disease is characterized by an intense airway inflammatory response mediated by neutrophils and chronic respiratory infections caused by P. aeruginosa . High levels of the complement component C5a, the strongest neutrophil chemoattractant molecule, are commonly found in the CF lung and have been associated with a worsening of the disease. In this study, we investigated how the isolates from CF patients modulate the levels of C5a and identified the bacterial factors i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Limiting any inflammation or immunopathology associated with complement activation may be beneficial for maintaining barrier integrity. Nevertheless, significant levels of complement and its breakdown components are found in the respiratory tract after many different infections (58)(59)(60). This means that complement can be activated in the respiratory tract and so in some circumstances may have negative impacts on the host.…”
Section: Discussionmentioning
confidence: 99%
“…Limiting any inflammation or immunopathology associated with complement activation may be beneficial for maintaining barrier integrity. Nevertheless, significant levels of complement and its breakdown components are found in the respiratory tract after many different infections (58)(59)(60). This means that complement can be activated in the respiratory tract and so in some circumstances may have negative impacts on the host.…”
Section: Discussionmentioning
confidence: 99%
“…Two immune-related negative regulatory genes, C5ar1-Like and EPX-Like , were screened from the immune-related genes in the combined analysis of DMRs-DEGs. C5a anaphylatoxin as a potent soluble mediator triggered chemotactic inflammation and the innate immune response via effecting inflammatory cell chemotaxis, chemokine release, phagocytosis as well as recruiting neutrophils and macrophages ( 35 , 36 ). As a specific receptor of C5a, C5ar could cause pro-inflammatory activation after specific binding with C5a in grass carp and zebrafish ( 37 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that, in vitro, LasB cleaves C1q and C3, both in the soluble phase and bound to bacterial surfaces [ 79 , 80 , 81 ]. In addition, LasB inactivates the purified components C5a [ 82 ], C5, C8, and C9 [ 79 ].…”
Section: Complement Evasion Strategies Of P Aeruginosamentioning
confidence: 99%
“…Degradation of the second complement component by AprA inhibits C3b formation and, subsequently, reduces bacterial opsonization, C5a formation, and neutrophil recruitment, allowing the bacteria to elude phagocytes [ 85 ]. Moreover, AprA cleaves C1q [ 80 , 85 ], C3 [ 81 , 85 ], and C5a [ 82 ].…”
Section: Complement Evasion Strategies Of P Aeruginosamentioning
confidence: 99%